Supported vaccination campaigns as panacea for rabies elimination: A case report (Agriculture, Food, and Natural Resources Journal, 2025)
Rabies, a zoonotic, transmissible viral disease of all warm-blooded animals, including humans, has continued to claim the lives of both animals and humans. Dogs have been identified as a major link for the continuous transmission of the disease; however, canine anti-rabies vaccination has proven to be pivotal in breaking the chain of transmission. A minimum of 70% anti-rabies vaccination coverage is required to create herd immunity. We conducted a supported anti-rabies vaccination campaign in the Nigeria Police Force Veterinary Clinic, Ilorin, between 28th September and 7th October 2022, supported by the Department of Veterinary Services, Kwara State Ministry of Agriculture. A total of 38 animals were presented; 37 were vaccinated, comprising 36 dogs and a cat. We declined vaccinating a dog due to its recent vaccination status. 56% of the vaccinated dogs were males; 24-25-month-old dogs dominate the vaccinated dogs with 25%. German shepherds and Caucasians were the most vaccinated dog breeds, and 72% of all the dogs have never been vaccinated. We concluded that supported free anti-rabies vaccination campaigns are important in achieving rabies elimination by 2030.
Keywords: One health; Rabies elimination; Supported vaccination; Vaccination coverage